Krisis Keadilan dalam Perlindungan Data Pribadi dan Ketimpangan Sosial di Era Ekonomi Digital - Akbar Nugroho Santoso; Reza Mahardika Putranto (Hakim: Jurnal Ilmu Hukum dan Sosial, 2025)
The rapid expansion of the digital economy has transformed personal data into a strategic economic asset, intensifying concerns over privacy, inequality, and justice in data protection systems. In developing countries, the growth of data-driven platforms often outpaces regulatory readiness and digital literacy, creating structural vulnerabilities among users. This study aims to analyze the crisis of justice in personal data protection by examining the relationship between social inequality, digital literacy, and regulatory strength in shaping data exploitation risks. The research adopts a socio-legal approach combined with quantitative cross-sectional design using data collected from 1,200 respondents across five countries: Indonesia, India, Brazil, Nigeria, and the Philippines. Statistical analyses, including descriptive statistics, correlation, and multiple regression, were employed to evaluate the relationships among variables. The findings indicate that countries with higher regulatory and enforcement scores, such as Brazil (regulation = 7.31; enforcement = 6.82), tend to experience lower data breach cases (290 per 100,000), while countries with weaker enforcement, such as Nigeria (4.88), show higher cases (402 per 100,000). At the individual level, low-income groups exhibit higher risk scores (mean = 5.18) compared to middle-income (3.63) and high-income groups (2.14). Additionally, global data breach cases increased significantly from 130 cases in 2018 to 920 cases in 2024, reflecting a consistent upward trend. These results demonstrate that data protection risks are unevenly distributed and strongly influenced by structural and individual factors. The study contributes by integrating a socio-legal framework with empirical analysis to propose a digital justice model that emphasizes the interplay between regulation, literacy, and inequality in ensuring fair and inclusive data protection.